Fabrication of bilayer tetrathiafulvalene integrated surface covalent organic frameworks. Issue 26 (17th June 2016) - Dong, Wei-Long; Li, Shu-Ying; Yue, Jie-Yu; Wang, Cheng; Wang, Dong; Wan, Li-Jun
Abstract : A bilayer covalent organic framework (COF) of TTF-based building blocks was obtained by imine reaction between tetrathiafulvalene tetraaldehyde (4ATTF) and p -phenylenediamine (PPDA). Abstract : A bilayer covalent organic framework (COF) of TTF-based building blocks was obtained by imine reaction between tetrathiafulvalene tetraaldehyde (4ATTF) and p -phenylenediamine (PPDA). Direct evidence for the eclipsed stacking of bilayer structure via π–π interaction between TTF units is provided by high resolution scanning tunneling microscopy.